Coordination, Fair Treatment and Inflation Persistence - John C. Driscoll; Steinar Holden (Norges Bank, 2002)
Most wage-contracting models with rational expectations fail to replicate the persistence in inflation observed in the data. We argue that coordination problems and multiple equilibria are the keys to explaining inflation persistence. We develop a wage-contracting model in which workers are concerned about being treated fairly. This model generates a continuum of equilibria (consistent with a range for the rate of unemployment), where workers want to match the wage set by other workers. If workers' expectations are based on the past behavior of wage growth, these beliefs will be self-fulfilling and thus rational. Based on quarterly U.S. data over the period 1955-2000, we find evidence that inflation is more persistent between unemployment rates of 4.7 and 6.5 percent, than outside these bounds, as predicted by our model.
hdl:11250/2498662
Keywords: E31; E3; E5; 330; inflation persistence; coordination problems; adaptive expectations